2017
DOI: 10.1016/j.cell.2017.03.042
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Lineage Infidelity Drives Wound Repair and Cancer

Abstract: Summary Tissue stem cells contribute to tissue regeneration and wound repair through cellular programs that can be hijacked by cancer cells. Here, we investigate such a phenomenon in skin, where during homeostasis, stem cells of epidermis and hair follicle fuel their respective tissues. We find that breakdown of stem cell lineage confinement - granting privileges associated with both fates - is not only hallmark, but also functional in cancer development. We show that lineage plasticity is critical in wound re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
310
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 291 publications
(325 citation statements)
references
References 64 publications
(110 reference statements)
15
310
0
Order By: Relevance
“…Genetic alterations that mobilize SCs more rapidly are often associated not only with accelerated wound repair, but also increased cancer susceptibility 30 . Indeed, individuals with gain-of-function mutations in inflammasome components can show increased risk of epidermal cancers 31, 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Genetic alterations that mobilize SCs more rapidly are often associated not only with accelerated wound repair, but also increased cancer susceptibility 30 . Indeed, individuals with gain-of-function mutations in inflammasome components can show increased risk of epidermal cancers 31, 32 .…”
Section: Discussionmentioning
confidence: 99%
“…In this view, the versatility of a stem cell in a wound response may then simply be a reflection of changes in this environment. When stem cells are removed from their native context, either in a wound response or in culture, they then must adjust their chromatin dynamics and change their program of gene expression in order to survive in their new environment (Adam et al, 2015; Ge et al, 2017). Given that not all epigenetic adjustments are rapid, this could account for why aging keratinocytes in vitro are initially readily distinguishable from their younger counterparts, but with time and passage in culture, these differences wane (Keyes et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Integrins α5β1 cluster at the leading edge of the keratinocyte, where they participate in polarizing cell shape and cytoskeletal movements needed for effective epithelial migration and fibronectin assembly (Aragona et al, 2017; Coles et al, 2006; Heller et al, 2014; Qiao et al, 2014). Finally, RNA-seq analyses of microdissected tissue in the migrating zone suggests that a number of metalloproteinases are expressed, where they likely function in the ECM remodeling that takes place in the wound repair process (Aragona et al, 2017; Ge et al, 2017; Hattori et al, 2009; Okada et al, 1997; Stevens and Page-McCaw, 2012). …”
Section: Contribution and Dynamics Of Skin Stem Cells During Homeostamentioning
confidence: 99%
See 1 more Smart Citation
“…Besides that, injured and cancer tissues have similar gene signatures. It was recently shown that SC lineages acquire plasticity that enables their activation, which is facilitated by SOX9 and KLF5 transcription factors in both phenomena: wound healing and tumorigenesis (58).…”
Section: Skin Carcinogenesis In Nude Mouse Modelmentioning
confidence: 99%